Single-Wavelength and Multiwavelength Q-Switched Fiber Laser Using Fe3O4 Nanoparticles - Yushan Chen; Jinde Yin; Hao Chen; Jinzhang Wang; Peiguang Yan; Shuangchen Ruan (IEEE Photonics Journal, 2017)
We demonstrate a simple Fe3O4 nanoparticles (FONPs) based Q-switched fiber laser that is able to generate stable nanosecond pulses with single-wavelength or multiwavelength regimes. In the single-wavelength lasing scheme, the fiber laser generates 613-ns pulse with average output power of 41.2 mW, pulse energy of 321.3 nJ, and signal-noise-ratio of 54.4 dB. In the multiwavelength lasing scheme, stable pulse is achieved with 18-wavelength channels contained within the 3-dB bandwidth range. Our results prove that the FONPs can act as an effective Q-switch for high-energy pulse generation.